2022
DOI: 10.7759/cureus.25428
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Arterial Spin Labeling Functional MRI in Assessing Perfusion Impairment of Renal Allografts: A Systematic Review

Abstract: Arterial spin labeling (ASL) is a functional magnetic resonance imaging (fMRI) technique that uses water in arterial blood as a tracer to map an area of interest where the intravascular and extravascular compartments exchange. Our review article focuses primarily on the role of ASL fMRI in assessing perfusion impairment in renal allografts in order to take appropriate steps to eliminate the cause of perfusion impairment at an early stage, thereby extending graft life. The study also highlights various other fM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Based on this knowledge, a pilot study lead by Brown et al paired MRE technology to arterial spin labeling (ASL), a noninvasive fMRI technique through which RBF can be reliably quantified and which promises early-stage detection of CKD [ 32 – 34 ]. In ASL, water in arterial blood is used as an endogenous tracer to map of regional perfusion [ 35 , 36 ]. Two image types are captured: a contrast-free control image and a labeled image in which an electromagnetic pulse magnetizes arterial blood [ 36 ].…”
Section: Mrimentioning
confidence: 99%
“…Based on this knowledge, a pilot study lead by Brown et al paired MRE technology to arterial spin labeling (ASL), a noninvasive fMRI technique through which RBF can be reliably quantified and which promises early-stage detection of CKD [ 32 – 34 ]. In ASL, water in arterial blood is used as an endogenous tracer to map of regional perfusion [ 35 , 36 ]. Two image types are captured: a contrast-free control image and a labeled image in which an electromagnetic pulse magnetizes arterial blood [ 36 ].…”
Section: Mrimentioning
confidence: 99%
“…Blood supply to the kidneys comes from a single system, is distributed between segments, and has no collateral circulation, providing a theoretical basis for the application of ASL [32]. ASL allows for the noninvasive measurement of the local blood perfusion of the kidney, and its repeatability and reliability have been recognized by most scholars [16,[33][34][35][36]. At present, ASL has been preliminarily applied in the diagnosis of acute and chronic kidney injury [16], obstructive hydronephrosis [33], kidney tumor [34], kidney allograft [35], and RAS [36].…”
Section: Arterial Spin Labeling For Renal Function Assessmentmentioning
confidence: 99%
“…ASL allows for the noninvasive measurement of the local blood perfusion of the kidney, and its repeatability and reliability have been recognized by most scholars [16,[33][34][35][36]. At present, ASL has been preliminarily applied in the diagnosis of acute and chronic kidney injury [16], obstructive hydronephrosis [33], kidney tumor [34], kidney allograft [35], and RAS [36]. Some researchers have found that the RBF values of the renal cortex and medulla in patients with acute kidney injury were markedly lower than those in the control group [37].…”
Section: Arterial Spin Labeling For Renal Function Assessmentmentioning
confidence: 99%
“…3 A recent meta-analysis reviews the role of ASL in assessing perfusion impairment in renal allografts, indicating that compared with healthy kidney transplant patients, renal ASL perfusion values were significantly lower in subjects with the functional imbalance of kidney transplants, with a positive correlation in the estimated glomerular filtration rate. 4 In this issue, the authors assess the significance of ASL in 46 patients, in order to discriminate those with posttransplant allograft dysfunction who need biopsy from those who do not. 5 Cortical ASL in the group who needed biopsy was significantly lower than in the other group.…”
mentioning
confidence: 99%
“…Several ASL imaging techniques have been shown to get a reliable measurement of the renal perfusion for both healthy volunteers and those patients with one or more of the following pathologies: renal diseases, arterial stenosis, renal neoplasms, and allografts 3 . A recent meta‐analysis reviews the role of ASL in assessing perfusion impairment in renal allografts, indicating that compared with healthy kidney transplant patients, renal ASL perfusion values were significantly lower in subjects with the functional imbalance of kidney transplants, with a positive correlation in the estimated glomerular filtration rate 4 …”
mentioning
confidence: 99%